(untitled) (Research, Society and Development, 2022)
Introduction: The research presents an evaluation, based on bibliographic studies, on breastfeeding up to six months and the impact on child development. Objective: To present the importance of exclusive breastfeeding, early weaning and its consequences for children. Methodology: For the construction of the article, a literature review was used, based on research on scientific article websites, for example, Scielo, PubMed, Governmental Agencies and Magazines, through a search for information relevant to the topic. Results and Discussion: 43 references related to the topic were analyzed, the results found in the articles showed that babies breastfed on exclusive breastfeeding until 06 months of age had a better development than those breastfed until 04 months or even those who did not breastfeed at first year of life. Conclusion: Exclusive breastfeeding is extremely important for the mother and her baby, this breastfeeding connection protects the baby from respiratory infections, reduces the risk of allergies and is linked to optimal motor development for the child, therefore mothers should actively breastfeed their children, to obtain the above benefits.